Can video thermography improve differential diagnosis and therapy between basal cell carcinoma and actinic keratosis?. Issue 5 (9th June 2014) - Di Carlo, Aldo; Elia, Fulvia; Desiderio, Flora; Catricalà, Caterina; Solivetti, Francesco M.; Laino, Luigi
Abstract Various noninvasive techniques (dermoscopy, confocal microscopy, etc.) have been introduced to help the clinical diagnosis in nonmelanoma skin cancer. Among them, the high definition video thermographic technique (VTG) has recently been proposed. The aim of this study is to define the VTG patterns, respectively of actinic keratosis (AK) and basal cell carcinoma (BCC), and to compare these data with them of dermoscopy. The study included 36 patients with a total number of 135 lesions who underwent clinical, VTG, and dermoscopic examination. The VTG showed the presence of a hyperthermic pattern in all the cases of AK, while in the case of the BCC, the pattern was hypothermic. Dermoscopy also showed distinct pattern for AK and for BCC, but in 22% of them the data were not conclusive. Our study permits us to define two specific VTG patterns, BCC and AK respectively.